Internal devaluation and economic inequality in Portugal: challenges to industrial relations in times of crisis and recovery - Campos Lima, M. Da P. (2021)
Internal devaluation policies imposed in southern European countries since 2010 have weakened labour market institutions and intensified wage inequality and the falling wage share. The debate in the wake of the financial and economic crisis raised concerns about slow wage growth and per- sistent economic inequality. This article attempts to shed light on this debate, scrutinising the case of Portugal in the period 2010–2017. Mapping the broad developments at the national level, the article examines four sectors, looking in particular at the impact of minimum wages and collective bargaining on wage trends vis-a`-vis wage inequality and wage share trajectories. We conclude that both minimum wage increases and the slight recovery of collective bargaining had a positive effect on wage outcomes and were important in reducing wage inequality. The extent of this reduction was limited, however, by uneven sectoral recovery dynamics and the persistent effects of pre- carious work, combined with critical liberalisation reforms.